2002
DOI: 10.1002/adma.200290017
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Optical Properties of Self‐Organized Au2Si Nanospheres Pea‐Podded in a Silicon Oxide Nanowire

Abstract: There is a great impetus in the research on semiconductorbased nanostructures due to their unusual optoelectronic properties that result from quantum size effects.[1] The recent success of silicon-based nanostructures [2±6] with interesting optical [7,8] and electronic [9] properties has renewed interest in this relevant field of study. Exotic structures of silicon-based nanowires with self-organized silicon nanospheres have also been reported [10] furthering the ªbottom±upº paradigm for device fabrication. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 21 publications
10
56
3
Order By: Relevance
“…Similar Au sphere in silica structures have been previously observed 16,[27][28][29] and with microwave synthesis methods, "pea-pod" structures have been demonstrated with other metals and insulators. 16 Under ultra-high vacuum conditions, Au migration on Si nanowires was observed to play an important role in the growth and resulting structure of the nanowire.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Similar Au sphere in silica structures have been previously observed 16,[27][28][29] and with microwave synthesis methods, "pea-pod" structures have been demonstrated with other metals and insulators. 16 Under ultra-high vacuum conditions, Au migration on Si nanowires was observed to play an important role in the growth and resulting structure of the nanowire.…”
Section: Introductionsupporting
confidence: 62%
“…We hypothesize a nanosphere formation process similar to that first suggested by Wu et al 27 , but initiated sequentially near the reservoir by the process illustrated in Fig. 5.…”
Section: Formation Of Au Nanospheres In Silica Nanowiresmentioning
confidence: 91%
See 2 more Smart Citations
“…Ag@TiO 2 core@shell NFs have been prepared by TiO 2 deposition at 130 ºC over a silver metal foil that had been previously exposed to a plasma of oxygen [46,47]. Formation of gold-nanoparticle-embedded dielectric nanowires and other related "peapod" nanostructures is an active area of research because of their multiple applications in various fields [37,61,62]. In our previous works by plasma deposition it was shown that oxygen plasma treatments provoke the development of silver surface nanostructures and a high accumulation of mechanical stress at its surface because of the higher specific volume of silver oxide as compared with metal silver.…”
Section: Formation Of Supported Core@shell (Metal/oxide (Ag@tio 2 )) mentioning
confidence: 99%